Whey Protein Complexes with Green Tea Polyphenols: Antimicrobial, Osteoblast-Stimulatory, and Antioxidant Activities - Carson, Matthew; Keppler, Julia K; Brackman, Gilles; Dawood, Daniel; Vandrovcova, Marta; Fawzy El-Sayed, Karim; Coenye, Tom; Schwarz, Karin; Clarke, Susan A; Skirtach, Andre G; Douglas, Timothy E L (Cells, tissues, organs, 2018)
Polyphenols are known for their antimicrobial activity, whilst both polyphenols and the globular protein β-lactoglobulin (bLG) are suggested to have antioxidant properties and promote cell proliferation. These are potentially useful properties for a tissue-engineered construct, though it is unknown if they are retained when both compounds are used in combination. In this study, a range of different microbes and an osteoblast-like cell line (human fetal osteoblast, hFOB) were used to assess the combined effect of: (1) green tea extract (GTE), rich in the polyphenol epigallocatechin gallate (EGCG), and (2) whey protein isolate (WPI), rich in bLG. It was shown that approximately 20-48% of the EGCG in GTE reacted with WPI. GTE inhibited the growth of Gram-positive bacteria, an effect which was potentiated by the addition of WPI. GTE alone also significantly inhibited the growth of hFOB cells after 1, 4, and 7 days of culture. Alternatively, WPI significantly promoted hFOB cell growth in the absence of GTE and attenuated the effect of GTE at low concentrations (64 µg/mL) after 4 and 7 days. Low concentrations of WPI (50 µg/mL) also promoted the expression of the early osteogenic marker alkaline phosphatase (ALP) by hFOB cells, whereas GTE inhibited ALP activity. Therefore, the antioxidant effects of GTE can be boosted by WPI, but GTE is not suitable to be used as part of a tissue-engineered construct due to its cytotoxic effects which negate any positive effect WPI has on cell proliferation.
Keywords: dospělí; Polyphenol; Catechin; proliferace buněk; Antioxidants; buněčné linie; Adult; Antioxidant; osteogeneze; mladý dospělý; osteoblasty; Fibroblasts; syrovátkové proteiny; Polyphenols; buněčná diferenciace; lidé; Antibacterial properties; Tea; Whey protein isolate; Anti-Bacterial Agents; fibroblasty; kultivované buňky; katechin; Whey Proteins; Osteoblast; Cell Line; Cells, Cultured; Male; Osteoblasts; Bacteria; Young Adult; antioxidancia; Cell Proliferation; polyfenoly; Cell Differentiation; Osteogenesis; mužské pohlaví; antibakteriální látky; čaj; Humans